Applying augmented reality to enhance learning: a study of different teaching materials. (27th December 2016) - Hung, Y.‐H.; Chen, C.‐H.; Huang, S.‐W.
Abstract: The objective of this study was to determine the usefulness of augmented reality (AR) in teaching. An experiment was conducted to examine children's learning performances, which included the number of errors they made, their ability to remember the content of what they had read and their satisfaction with the three types of teaching materials, including a picture book, physical interactions and an AR graphic book. The three teaching materials were aimed to respectively demonstrate the characteristics of six bacteria with 2D graphics, 3D physical objects, and 3D virtual objects. Seventy‐two fifth‐grade children were randomly selected to participate in the study, and they were divided into three groups, each of which used the assigned teaching material to learn the name of the six different bacteria in intervals of 1, 2 and 3 min. Results showed that the AR graphic book offers a practical and hands‐on way for children to explore and learn about the bacteria. Follow‐up interviews indicated that the children liked the AR graphic book the most, and they preferred it to the other materials. Lay Description: What is currently known about Augmented Reality and learning?: Augmented reality (AR) provides a new perspective for learning by allowing learners to visualize complex spatial relationships and abstract concepts. What the paper adds to the subject matter?: AR improves learning performances to a similar extent as the most used teaching materials (both picture books and physical interactions) do. AR not only facilitates learning but also increases learning motivations better than conventional teaching materials do. The implications of study findings for practitioners: If children feel bored about reading textbooks, give them AR (because AR effectively enhances learning and children are more motivated when using AR). AR teaching material is a good alternative to conventional picture book and physical interactions.